Emerging energy applications of two-dimensional layered materials - Late, Dattatray J.; Rout, Chandra Sekhar; Chakravarty, Disha; Ratha, Satyajit (Canadian Chemical Transactions, 2015)
Atomically thin semiconducting transition metal dichalcogenides (TMDCs) layered materials have recently been emerged as an exciting area of research due to accessibility for easy synthesis using various chemical and physical methods. These two-dimensional (2D) layered materials with single layer have direct and wide band gap due to which, they are more suitable for nanoelectronics and optoelectronics device applications. Here, we present a review of the energy related aspects of atomically thin layered materials like MoS2, WS2, MoSe2, WSe2, InSe, GaSe, GaTe, MoTe2, WTe2 etc. for supercapacitor, solar cell, lithium ion battery and water splitting application. By significantly assessing various materials and comparing their performances with challenging technology, the advantages and disadvantages of this promising area of energy materials are recognized, which may provide guidelines for future progress.

Exfoliation of bulk inorganic layered materials into nanosheets by the rapid quenching method and their electrochemical performance - Chakravarty, Disha; Late, Dattatray J. (European Journal of Inorganic Chemistry, 2015)
We report herein the results of our investigations on the synthesis of transition-metal dichalcogenide (TMDC) semiconductor layered materials of MoS2, WS2, MoSe2, and WSe2 by the rapid quenching method. The bulk powders were added to deionized water in a polypropylene tube and subsequently flushed with argon gas. Thirty rapid freezing (30 s in a liquid nitrogen bath) and heating (20 min in an oil bath at 60 degrees C) cycles were then carried out. The reaction product was obtained in a yield in excess of 60 wt.-%, which indicates that the method can be utilized on an industrial scale for the production of 2D nanosheets. The as-synthesized products were then characterized by TEM, which revealed nanosheet-like morphologies. Raman spectroscopy confirmed the high quality of the nanosheet samples. The exfoliated samples also showed good electrochemical performance. Of the TMDC samples investigated, the WSe2 nanosheets were found to give the best performance due to their uniform morphology, large surface area, and fewest number of defects.
Keywords: chalcogenides; Electrochemistry; Layered compounds; Molybdenum; Nanostructures; Tungsten